Effect of Changes in Air Temperature on Fuel Consumption and HC and Co Exhaust Gas Emissions - Sembiring, Resep; Munthe, Immanuel; Surbakti, Adnan; Ginting, Tinus; Pasaribu, Sabar (International Journal of Engineering, Science and Information Technology, 2024)
Motorized vehicles are generally equipped with a driving engine which functions as a driver for the car. Motorized vehicles have engines consisting of one cylinder, two cylinders, three cylinders, and so on, and all of them require air as a medium for burning fuel in the combustion chamber to produce power to drive the vehicle. Motorized vehicles, both at sea and on land, operate at different air temperatures in all corners of the earth. This research was carried out by varying the air temperature entering the combustion chamber. The intended temperatures are 20oC, 25oC, 30oC, 35oC, and 40oC, and what will be examined is fuel consumption, HC, and CO exhaust emissions. The research results show that air temperatures from 20 to 40 degrees do not significantly affect fuel consumption or HC and CO exhaust emissions.